Finite element analysis of defective die-casted AlSi9Cu3 (ADC12) steering housings - Yasmin Syazwani, Binti Mohamad (Universiti Malaysia Sarawak (UNIMAS), 2017)
Die casting process is one of a manufacturing process which is important in producing a large amount of product especially complex parts. The quality of the components in vehicles is important to ensure their safe functionality. The state of products from the casting process will determine the effectiveness to be used in everyday life. This study of the defective die-casted material with different level of porosity which concentrated on their behaviour to perceive strength limits by finite element analysis method was carried out. The outcomes such as total deformation, stress, elastic strain, shear stress and strain energy also being included in this study. In order to achieve the objectives of this study, the simulation of analysis are conducted by using commercialize computer simulation software, ANSYS software. The results are compared and discussed. The analysis can provide the awareness on effects of defective products and ensure high quality production in the future for manufacturing sectors.